Modified chitosan hydrogels as drug delivery and tissue engineering systems: present status and applications - Tapan Kumar Giri; Amrita Thakur; Amit Alexander; Ajazuddin; Hemant Badwaik; Dulal Krishna Tripathi (Elsevier, 2012)
Chitosan, a natural cationic polysaccharide, is prepared industrially by the hydrolysis of the aminoacetyl groups of chitin, a naturally available marine polymer. Chitosan is a non-toxic, biocompatible and biodegradable polymer and has attracted considerable interest in a wide range of biomedical and pharmaceutical applications including drug delivery, cosmetics, and tissue engineering. The primary hydroxyl and amine groups located on the backbone of chitosan are responsible for the reactivity of the polymer and also act as sites for chemical modification. However, chitosan has certain limitations for use in controlled drug delivery and tissue engineering. These limitations can be overcome by chemical modification. Thus, modified chitosan hydrogels have gained importance in current research on drug delivery and tissue engineering systems. This paper reviews the general properties of chitosan, various methods of modification, and applications of modified chitosan hydrogels.